Kelimpahan dan Keanekaragaman Spesies Laba-laba Predator Hama Padi Ratun di Sawah Pasang Surut - Siti Herlinda; Hendri Candro Nauli Manalu; Rinda Fajrin Aldina; . Suwandi; Andi Wijaya; . Khodijah; Dewi Meidalima (Universitas Lampung, 2014)
ABSTRACTAbundance and Species Diversity of Predatory Spiders for Insect Pests Inhabiting Ratoon Paddy in Tidal Lowland. Ratoon paddy productivity is lower than the main crop. Increasing productivity of the ratoon paddy is to protect the paddy from pests and diseases. This study aimed to analyze the abundance and species diversity of predatory spiders of rice pests on ratoon paddy in tidal lowland. Ratoon paddy field observed was from the main crop that has been harvested and cut 20 cm height. Paddy area observed was 2 ha field planted using Ciherang and Inpara varieties. Spiders inhabiting canopy were sampled using insect nets but soil dwelling spiders were trapped using pitfall traps. The result showed that spider species inhabiting canopy of ratoon paddy were Pardosa pseudoannulata, Lycosa chaperi, Araneus inustus, Cylosa insulana, Atypena adelinae, Erigone bifurca, Erigonidium graminicola, Oxyopes javanus, Argyrodes miniaceus, and Marpisa magister. Spider species found soil dwelling were 11 species, namely Pardosa pseudoannulata, Pardosa sumatrana, Pardosa mackenziei, Pardosa oakleyi, Hogna rizali, Araneus inustus, Cylosa insulana, T. vermiformis, Runcinia albostriata, Coleosoma octomaculatum, and Marpisa magister. Abundance, species number, species diversity for soil dwelling spiders were higher than those for canopy inhabiting spiders. However, the abundance, species number, species diversity for the soil dwelling spiders tended to be higher on the ratoon paddy 3, 4, and 5 week old than those on 1, 2, and 6 week old. From the result, we concluded that abundance, species number, species diversity of spiders found in the ratoon paddy were higher or tended similar to those on the main crop.